(untitled) (International journal of artificial intelligence, 2025)
Needs analysis is a fundamental step in the design of English for Specific Purposes (ESP) courses, ensuring that instruction aligns with learners’ academic, professional, and occupational language requirements. This paper explores the critical role of needs analysis in shaping ESP curricula, teaching strategies, and assessment practices. By gathering data from learners and relevant stakeholders, educators can identify linguistic gaps, tailor authentic materials, and promote learner motivation. Although challenges such as time constraints and mixed-proficiency groups exist, needs analysis remains an essential tool for creating relevant, goal-oriented ESP instruction that enhances communicative competence in real-world contexts.